The Emerging Landscape of Edge-Computing - Noghabi, Shadi; Cox, Landon; Agarwal, Sharad; Ananthanarayanan, Ganesh (ACM SIGMOBILE GetMobile, 2020)
Edge computing is a trending notion introduced a decade ago as a new computing paradigm for interactive mobile applications. The initial vision of the edge was a multi-tenant resource that will be used opportunistically for low-latency mobile applications. Despite that vision, we see in practice a different set of applications, driven by large-scale enterprises, that have emerged and are driving real-world edge deployments today. In these applications, the edge is the primary place of storage and computation and if network conditions allow, the cloud is opportunistically used along-side. We show how these enterprise deployments are driving innovation in edge computing. Enterprise-driven scenarios have a different motivation for using the edge. Instead of latency, the primary factors are limited bandwidth and unreliability of the network link to the cloud. The enterprise deployment layout is also unique: on-premise, single-tenant edges with shared, redundant outbound links. These previously unexplored characteristics of enterprise-driven edge scenarios open up a number of unique and exciting future research challenges for our community.